Soil behavior and geo-micromechanics : proceedings of sessions of GeoShanghai 2010, June 3-5, 2010, Shanghai, China - Meier, Roger; Abbo, Andrew; Wang, Linbing, 1963- (Geotechnical special publication ;, 2010)
Soil Behavior and Geo-Micromechanics contains 41 papers addressing many different areas of soil behavior, constitutive modeling, and geo-micromechanics. The papers in this Geotechnical Special Publication range from experimental studies of soil shear strength and compressibility to theoretical advances in BiotÆs consolidation theory and constitutive modeling. The research described in this proceedings advances our understanding of soil as an engineering material and improves our ability to model the behavior of soil in slopes, foundations, and earth structures.